Evaluation of a pre-post quasi-experimental educational intervention on breast cancer awareness among pharmacy professionals in Karachi, Pakistan - Mansoor, Noor us Saba; Naveed, Safila; Ali, Huma; Manzoor, Ammara; Zahoor, Saima; Sheikh, Javeria (Frontiers in Public Health, 2024)
Introduction Cancer, particularly breast cancer, is a major contributor to mortality and a significant impediment to life expectancy. In 2020, breast cancer accounted for 11.7% of all cancer cases and caused approximately 685,000 deaths worldwide, surpassing lung cancer in prevalence. The study aims to evaluate the impact of an educational intervention on breast cancer awareness among pharmacy students by comparing their understanding before and after the program. Method A pre-post quasi-experimental study was designed to assess knowledge and awareness of breast cancer, breast self-examination (BSE) practices, and attitudes toward breast cancer among female university students in Karachi, Pakistan. Participants completed a pre-session questionnaire, attended an awareness workshop and video tutorial, and then completed a post-session questionnaire 2 weeks later. Results Of 1,200 participants, 1,015 of them completed both the pre- and post-intervention questionnaires. Key demographic features included 83.9% of the participants being in the 18–24 age group, 26.8% being married, and only 14.2% having a family history of breast cancer. Before the intervention, 60.7% of the participants were not involved in regular breast self-exams due to a lack of awareness. Post-intervention results showed a significant increase in awareness, with 35.9% rising to 94.9%. The use of screening methods increased from 46.7 to 94.8%. Knowledge of breast cancer improved from 51.2 to 96.7%, and the general perception rose from 48.2 to 93.4%. Attitudes toward self-examination also shifted positively, indicating a significant change in perception. Interpretation and conclusion The study concludes the baseline knowledge of breast cancer among female students was inadequate but improved significantly from over 40% to over 90% following the educational intervention. The intervention positively influenced the general perception and attitudes toward breast cancer. These findings highlight the need for regular educational sessions to enhance awareness, improve healthcare outcomes, and reduce mortality rates, particularly in developing countries.